Impact of caregiver guidance on infection prevention in home care (Research, Society and Development, 2022)
Home care is an alternative to hospital admissions. Despite the multiple benefits, concerns about the risk of infections persist. Thus, the aim of this study was to assess the impact of supervised guidance on the care of patients hospitalized at home on the prevention of infections, using and comparing the conventional and systematic strategies. This is an experimental study with home care patients at Home Care service of a Medical Cooperative from Sergipe between May 2006 and April 2007. The patients included were divided into two groups, the control (group I) and the experimental (group II). Caregivers in group I received general guidelines, without standardization, while those in group II received guidelines systematized by the researcher. At the end, the occurrence of infections between the two groups was analyzed by an infectologist who was not aware of the allocation of patients in the groups. Forty-seven patients in group I, conventional, and 28 in group II, experimental, were evaluated. Infections were observed throughout the period of data collection in both groups and were diagnosed in 48.9% in group I and 17.9% in group II, with a significant difference between them and a relative risk of 2.7 for the occurrence of infection. Thus, this study showed a reduction in the occurrence of infections in the group that received systematic guidance in relation to the group that received general guidance, noting the effectiveness of this strategy.